EVALUASI TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 DAN ITIL V3 2011 PADA PT. BALI UNGGUL SEJAHTERA - Maulana Hendarwan, Iqbal; Jayantara Adiputra, A A Bagus; Endika Ginting, Alloy; Arsa Suyadnya, I Made; Shandyasa, I Wayan (Jurnal SPEKTRUM, 2024)
The evaluation process of information technology governance can be conducted using the domains within the COBIT 5 and ITIL V3 2011 frameworks. In this research, The process of evaluation was discussed to ensure the efficient functioning of information technology governance at PT. Bali Unggul Sejahtera using several domains from the COBIT 5 and ITIL V3 2011 frameworks. The aim of this research is to identify issues in the governance and information technology services at PT. Bali Unggul Sejahtera, determine the maturity level of IT processes using relevant domains from the COBIT 5 and ITIL V3 2011 frameworks through Gap Analysis and establish recommendations for activities as a reference for future improvements. In the COBIT 5 framework, researchers use sub-domains APO12, DSS01 and DSS05. In the ITIL V3 2011 framework, researchers use sub-domains Service Design 4.7, Service Operation 4.1 and Service Operation 6.2.1.3. The results of this research, The APO12 sub-domain COBIT 5 framework is currently at maturity level 3, the DSS01 and DSS05 sub-domains are currently at maturity level 4. In the ITIL V3 2011 framework, the sub-domains Service Design 4.7, Service Operation 4.1 and Service Operation 6.2.1.3 are currently at maturity level 4.). The results of this evaluation serve as recommendations for activities aimed at achieving the desired maturity level of 5 (Optimized).